The Influence of Company Size on Profit Information with Profit Management and Earnings Opacity as Intervening Variables - Kurniasih Dwi Astuti; Windu Mulyasari; Fadilatun Nisa (Journal of Applied Business, Taxation and Economics Research, 2022)
The study aims to know the influence size of the company from informative profit to informative profit with management profit and earnings opacity to the intervening variable. Size company be measured with the natural logarithm of total assets. Informative profit proxied with earnings response coefficient. Management profit proxied with discretionary accruals. Meanwhile, earnings opacity is proxied with income smoothing. Population in the study i.e. company manufacturers listed on the Indonesia Stock Exchange for the 2016-2020 period. The Retrieval technique sample used a purposive sampling technique where 42 companies were selected with a total sample of 210 research data. Data analysis techniques using multiple linear regression with SPSS software version 25 and analysis track use Sobel test online. Research results show that the size company, in a manner, direct have an influence positive to informative profit. However, management profit and earnings opacity have an influence negative to informative profit. Management profit and earnings opacity does not have a role as an intermediate intervening variable influencing the size company to informative gain.